Whales and waves: Humpback whale foraging response and the shoaling of internal waves at Stellwagen Bank. Issue 4 (2nd April 2015) - Pineda, Jesús; Starczak, Victoria; da Silva, José C. B.; Helfrich, Karl; Thompson, Michael; Wiley, David
Abstract: We tested the hypothesis that humpback whales aggregate at the southern flank of Stellwagen Bank (SB) in response to internal waves (IWs) generated semidiurnally at Race Point (RP) channel because of the presence of their preferred prey, planktivorous fish, which in turn respond to zooplankton concentrated by the predictable IWs. Analysis of synthetic aperture radar (SAR) images indicates that RP IWs approach the southern flank of SB frequently (∼62% of the images). Published reports of whale sighting data and archived SAR images point to a coarse spatial coincidence between whales and Race Point IWs at SB's southern flank. The responses of whales to IWs were evaluated via sightings and behavior of humpback whales, and IWs were observed in situ by acoustic backscatter and temperature measurements. Modeling of IWs complemented the observations, and results indicate a change of ∼0.4 m/s in current velocity, and ∼1.5 Pa in dynamic pressure near the bottom, which may be sufficient for bottom fish to detect the IWs. However, fish were rare in our acoustic observations, and fish response to the IWs could not be evaluated. RP IWs do not represent the leading edge of the internal tide, and they may have less mass‐transport potential than typical coastal IWs. There was large interannual variability in whale sightings at SB's southern flank, with decreases in both numbers of sightings and proportion of sightings where feeding was observed from 2008 to 2013. Coincidence of whales and IWs was inconsistent, and results do not support the hypothesis. Key Points: Internal waves regularly approach a bank, which is an ecological hotspot At short‐time scales, there was no relationship between whales and internal waves Large interannual variability in humpback whale sightings was observed at an ecological hotspot